Two-dimensional metal-dielectric hybrid-structured film with titanium oxide for enhanced visible light absorption and photo-catalytic application. (March 2016) - Park, Joonmo; Jun Kim, Hee; Nam, SangHyeon; Kim, Hyowook; Choi, Hak-Jong; Jang, Youn Jeong; Sung Lee, Jae; Shin, Jonghwa; Lee, Heon; Baik, Jeong Min
Abstract: Two-dimensional design based on ultrathin TiO2 film for enhanced visible light absorption and photo-catalytic applications is reported, which mainly consists of three layers of gold film, TiO2 film, and gold nanoparticles (Au NPs). The Au and TiO2 films are produced by e-beam evaporation and atomic layer deposition, respectively, in a carefully controlled way to minimize surface roughness. As compared with bare TiO2 film, the Au NPs/TiO2 /Au film significantly increased the photoactivity over the entire UV and visible wavelength range. The Au film increases the light absorption in the UV region with TiO2 acting as an impedance-matching layer, while the Au NPs increase the light absorption in the visible region due to the plasmonic resonance effects, increasing the photocurrent under visible light. 3D numerical simulation results suggest that the Au film also plays an important role in enhancing the electrical field intensity at the TiO2 film in contact with Au NPs, by efficient excitation of localized surface plasmon resonances, thereby, contributing to the enhanced photoactivity of the film in the visible range. This simple system may serve as an efficient platform for solar energy conversion utilizing the whole UV-visible range of solar spectrum based on two-dimensional plasmonic photoelectrodes. Graphical abstract: The table of contents entry: Two-dimensional metastructured film with Titanium Oxide is fabricated as a photo-catalytic photoanode with exceptional visible light absorption. The metastructured film consist of three layers of Au film, ultrathin TiO2 layer (20 nm), and Au nanoparticles (NPs), and shows high light absorption of about 90% in the visible range of 380–700 nm, while the Au film shows only 60 % in the wavelength of 380–500nm.